Preparation method of defective MOF (Metal Organic Framework)-based intrinsic microporous polymer mixed matrix membrane for efficient separation of propylene and propane

Defective MOFs are prepared by acid etching MOFs and blended with self-porous polymers, which solves the problem of insufficient interface compatibility of the mixed matrix membrane and achieves a significant improvement in the separation performance of aprolyte.

CN119819139AActive Publication Date: 2025-04-15DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510116175.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing mixed matrix membranes are insufficient interfacial compatibility in propylene separation, resulting in poor separation performance.

Method used

Defective MOF is prepared by acid etching MOF and blended with the electron-donating group-containing self-porous polymer to prepare a defective MOF-based self-porous polymer mixed matrix membrane. Open metal sites in defective MOFs enhance propylene adsorption capacity and coordinate with self-porous polymers to improve interface compatibility.

Benefits of technology

It significantly improved the propylene separation performance, broke through the upper limit of propylene/propane separation in 2003, and showed excellent separation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819139A_ABST
    Figure CN119819139A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of gas separation membranes, and discloses a preparation method of a defective MOF (Metal Organic Framework)-based polymer mixed matrix membrane with intrinsic micropores for efficiently separating propylene from propane. The defect MOF with a hollow nano-frame structure is prepared through acid etching of the MOF, and the defect MOF and an intrinsic microporous polymer containing an electron donating group are prepared into the mixed matrix membrane. Open metal sites in the defective MOF are coordinated with an intrinsic microporous polymer to improve the interfacial compatibility, and meanwhile, the open metal sites in the defective MOF are utilized to improve the adsorption capacity of propylene. The prepared membrane material shows excellent propylene-propane separation performance and is expected to be well applied to the field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane preparation and application, and discloses a method for preparing a defective MOF-based self-microporous polymer mixed matrix membrane for efficient separation of propylene and propane. Background Art

[0002] Propylene is one of the world's largest chemical products and an important basic chemical raw material. At present, the separation of propylene and propane mainly relies on cryogenic separation technology, but this technology has high energy consumption and a complex separation process. Since propylene and propane have only slight differences in physical and chemical properties (boiling points are -47.6℃ and -42.1℃ respectively; van der Waals diameters are and ), resulting in great difficulty in separation. According to statistics, the purification of propylene and ethylene alone accounts for 0.3% of global energy consumption, which is an energy-intensive separation process (Sholl, DS and RP Lively (2016). "Seven chemicals separations to change the world." Nature 532 (7600): 435-437.). Therefore, it is of great significance to develop low-energy consumption and high-efficiency separation technology.

[0003] As an efficient and low-energy separation method, membrane separation technology shows great application potential due to its small footprint and simple operation. Microporous polymers (such as high-free-volume polyimides and self-microporous polymers) are very promising membrane materials for propylene / propane separation, but their separation performance is limited by the trade-off between gas permeability and selectivity. To solve this problem, mixed matrix membranes (MMMs) came into being. They are composed of a flexible or semi-rigid polymer phase and a dispersed rigid high-performance filler phase (such as metal organic framework MOF). Through synergistic optimization, the separation performance is significantly improved. Despite this, MMMs still face the problem of insufficient interfacial compatibility. Therefore, improving interfacial compatibility becomes the key to optimizing the performance of MMMs.

[0004] MOF defect engineering is an emerging method to regulate the pore structure and adsorption properties of materials by introducing ligand or metal cluster defects. For example, acid-base post-treatment can introduce defects by acid / base treatment of MOF. The study of Vermoortele et al. showed that the removal of the regulator after synthesis can lead to a large number of coordination unsaturated metal sites (Vermoortele, F., et al. (2013).

[0005] "Synthesis Modulation as a Tool To Increase the Catalytic Activity of Metal-Organic Frameworks: The Unique Case of UiO-66(Zr)." Journal of the American Chemical Society 135(31): 11465-11468.). This method can not only enhance the porosity, but also create abundant open metal sites. However, in order to introduce the unique advantages of defective MOFs into propylene / propane gas membrane separation, it is necessary to select a suitable etching strategy, consider the impact of defective MOFs on the mixed matrix membrane and the required separation gas, and weigh the impact of etching degree on permeability and selectivity to best optimize gas separation performance.

[0006] Based on this, the present invention proposes a simple and efficient strategy: prepare defective MOF by acid etching MOF, and blend it with self-microporous polymer containing electron-donating groups to prepare high-performance mixed matrix membranes. The open metal sites in the defective MOF can enhance the propylene adsorption capacity, and at the same time coordinate with the self-microporous polymer to significantly improve the interfacial compatibility. The experimental results show that the defective MOF-based MMM has broken through the 2003 propylene / propane separation upper limit and exhibited excellent separation performance. Summary of the invention

[0007] In view of the problems of poor interface compatibility and insufficient propylene propane separation performance of existing mixed matrix membranes, the present invention proposes a defective MOF-based self-microporous polymer mixed matrix membrane for efficient separation of propylene propane and a preparation method thereof.

[0008] The main content of the present invention is: a defective MOF is prepared by acid etching MOF, and the defective MOF is blended with a self-microporous polymer containing an electron-donating group to prepare a defective MOF-based self-microporous polymer mixed matrix membrane. The open metal sites in the defective MOF can enhance the propylene adsorption capacity, and at the same time coordinate with the self-microporous polymer containing an electron-donating group to significantly improve the interfacial compatibility. The prepared defective MOF-based self-microporous polymer mixed matrix membrane exhibits excellent propylene and propane separation performance.

[0009] The technical solution of the present invention:

[0010] A method for preparing a defective MOF-based self-microporous polymer mixed matrix membrane for efficient separation of propylene and propane, comprising the following steps:

[0011] (1) Synthesis of MOF: Metal salt A and 2-methylimidazole are dispersed in a reaction medium, respectively, and the metal salt A solution is quickly poured into the 2-methylimidazole solution for stirring reaction to obtain a milky white suspension; centrifugation is performed using a centrifuge, followed by washing and centrifugation for purification several times, and drying is performed in a vacuum oven to obtain MOF nanoparticles;

[0012] Wherein, the metal salt A is zinc nitrate hexahydrate and / or cobalt nitrate hexahydrate;

[0013] The reaction medium is methanol and / or ethanol;

[0014] The molar ratio of metal salt A to 2-methylimidazole is 1:2-16;

[0015] The reaction temperature is 25°C;

[0016] The speed of the centrifuge was 10000 rpm, and the centrifugation time was 10 min;

[0017] The solvent used for washing was methanol;

[0018] The drying temperature is 80°C and the drying time is 24h;

[0019] (2) Acid etching of MOF: dissolving acid A in solvent A to obtain a colorless transparent solution; dispersing the MOF nanoparticles synthesized in step (1) in solvent A, and obtaining a uniform MOF suspension after ultrasonication; blending the colorless transparent solution with the MOF suspension, stirring the mixture at a certain temperature, collecting the mixture by centrifugation, washing the mixture with solvent A, centrifuging the mixture several times, and drying the mixture in a vacuum oven to obtain defective MOF particles after etching;

[0020] Wherein, acid A is one or a mixture of two or more of cyanuric acid, citric acid, glycine, gallic acid, and methyl gallate;

[0021] Solvent A is methanol and / or ethanol;

[0022] The molar ratio of acid A to MOF nanoparticles is 1:1-8;

[0023] The reaction time is 12-36h, and the reaction temperature is 25-80°C;

[0024] The speed of the centrifuge was 10000 rpm, and the centrifugation time was 10 min;

[0025] The drying temperature is 80°C and the drying time is 24h;

[0026] (3) Synthesis of amidoxime-based PIM-1 (AO-PIM-1): First, unmodified PIM-1 polymer was synthesized. 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, tetrafluoroterephthalonitrile and anhydrous potassium carbonate were added to a mixed solution of solvent B and solvent C. After stirring at room temperature to fully disperse, the mixture was reacted at a certain temperature under the atmosphere of protective gas A. After the reaction was completed, the product was washed with solvent A, dissolved in solvent D and allowed to stand, and then solvent A was added to precipitate, and then the mixture was reacted with solvent D. The obtained polymer is washed with deionized water, and finally vacuum dried in a vacuum oven to obtain a purified PIM-1 polymer; subsequently, the synthesized PIM-1 polymer is dissolved in solvent E, heated and dissolved in an atmosphere of protective gas A, and after the temperature gradually rises to the reaction temperature, a 50 wt % hydroxylamine aqueous solution is added dropwise to perform a reflux reaction; after the reaction is completed, the reaction is cooled to room temperature, the reactant is poured into solvent A for precipitation, vacuum filtered and washed with solvent A, and finally vacuum dried in a vacuum oven to obtain a flocculent or powdery AO-PIM-1 polymer;

[0027] The molar ratio of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, tetrafluoroterephthalonitrile and anhydrous potassium carbonate is 1:1:3; solvent B and solvent C are N,N-dimethylacetamide (DMAC) and toluene, respectively, with a mass ratio of 2:1;

[0028] Solvent D is chloroform; Solvent E is tetrahydrofuran;

[0029] Protective gas A is nitrogen;

[0030] The reaction temperature of PIM-1 was 155°C and the reaction time was 60 min;

[0031] The drying temperature of PIM-1 was 120 °C and the drying time was 24 h;

[0032] The reaction temperature of AO-PIM-1 was 69 °C and the reaction time was 2 h;

[0033] The dropping rate of the hydroxylamine aqueous solution was 1 mL / min;

[0034] The drying temperature of AO-PIM-1 was 120°C and the drying time was 24 h;

[0035] (4) Preparation of AO-PIM-1 membrane: AO-PIM-1 polymer was dissolved in solvent F to prepare a membrane casting solution, stirred to fully dissolve, filtered through a microporous membrane filter, and then ultrasonically defoamed. The solution was placed in an oven at a certain temperature to volatilize the solvent and form a membrane;

[0036] Wherein, solvent F is N,N-dimethylformamide and / or N,N-dimethylacetamide;

[0037] The mass fraction of AO-PIM-1 polymer in the casting solution is 2-5wt%;

[0038] The stirring time is 12-24h, and the ultrasonic time is 20min;

[0039] The evaporation temperature of the solvent is 50°C and the evaporation time is 24h;

[0040] (5) Preparation of DMMM: Activate the defective MOF synthesized in step (2) in a vacuum drying oven, and ultrasonically disperse it in solvent H to obtain a defective MOF dispersion; dissolve AO-PIM-1 in solvent F; blend the AO-PIM-1 solution filtered by a microporous membrane filter with the defective MOF dispersion, add the AO-PIM-1 solution to the defective MOF dispersion twice to prepare a casting solution, perform preliminary dispersion by ultrasound, stir to fully disperse, then perform ultrasonic degassing, let stand, pour into a culture dish, and let stand in an oven at a certain temperature to volatilize the solvent to form a film;

[0041] Among them, the ultrasound time was 30min;

[0042] The stirring time is 12-24h, and the standing time is 2h;

[0043] The temperature of the oven is 50°C and the volatilization time is 24h.

[0044] Compared with the prior art, the present invention has beneficial effects: compared with other mixed matrix membranes, the present invention prepares defective MOF by acid etching MOF. The open metal sites in the defective MOF can enhance the propylene adsorption capacity, and at the same time coordinate with the self-microporous polymer containing electron-donating groups, significantly improving the interfacial compatibility. The defective MOF-based self-microporous polymer mixed matrix membrane prepared thereby exhibits excellent propylene-propane separation performance, and has the advantages of simple preparation method, obvious effect, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 (a) is a schematic diagram of the preparation of defective ZIF-8-based AO-PIM-1 mixed matrix membrane;

[0046] Figure 1(b) is an upper limit graph of the defective ZIF-8-based AO-PIM-1 mixed matrix membrane for propylene and propane separation performance.

[0047] Figure 2 is a comparison of the SEM images of ZIF-8 (a) and DZIF-8 (b). The SEM image of DZIF-8 shows a hollow nanoframe structure, indicating that the etching was successfully performed.

[0048] Figure 3It is a comparison of the BET graphs of ZIF-8 and DZIF-8. The hysteresis loop presented by DZIF-8 is wider and more extensive, showing the hysteresis loop characteristics of microporous-mesoporous materials after etching, which is mutually confirmed with the SEM graph. DETAILED DESCRIPTION

[0049] The specific implementation of the present invention is further described below in conjunction with the accompanying drawings and technical solutions.

[0050] Gas separation performance test: The method used for the gas separation performance test in the present invention is a constant volume variable pressure method, the test temperature is 35° C., and the test pressure is 0.2 MPa.

[0051] Example 1

[0052] (1) Synthesis of AO-PIM-1 polymer: First, synthesize the PIM-1 polymer. Add 3.4 g of TTSBI (0.01 mol), 2.0 g of TFTPN (0.01 mol), and 4.15 g of anhydrous K2CO3 (0.03 mol) into a three-necked flask, then add 20 mL of anhydrous DMAC and 10 mL of toluene, and stir mechanically at room temperature for about 20 min. The mixture is reacted at 155°C and N2 atmosphere for 60 min. After the reaction, the product is initially washed in methanol, then dissolved in chloroform and allowed to stand for 12 h, and then methanol is added for reprecipitation and washing. Then, a light yellow solid is obtained by vacuum filtration and drying, and then washed with deionized water to remove residual salt. Finally, the purified PIM-1 product is obtained by vacuum filtration and vacuum drying at 120°C for 24 h. Secondly, the amidoxime-modified AO-PIM-1 polymer was synthesized. 1.0 g of PIM-1 was added to a three-necked flask, and then 65 mL of THF (bp 66 ° C) was added to dissolve it, and heated to 65 ° C under a nitrogen inert environment. When the polymer was completely dissolved, the temperature rose to 69 ° C and maintained for a period of time. Then, 10 mL of a 50 wt% hydroxylamine aqueous solution was added dropwise to the polymer solution using a constant pressure dropping funnel. A precipitate will form in the solution and will dissolve again after 20 minutes. The reaction mixture was refluxed at 69 ° C for 2 h. After the reaction was completed, the turbid solution was cooled to room temperature and poured into ethanol for precipitation. After vacuum filtration to obtain the precipitate, it was washed 3 times with 200 mL of ethanol, and the product was dried in an oven at 110 ° C for 3 hours to obtain a flocculent or powdery AO-PIM-1 product.

[0053] (2) Synthesis of defective ZIF-8 etched by cyanuric acid: 2.98 g Zn(NO3)2·6H2O (0.01 mol) and 6.56 g 2-methylimidazole (0.08 mol) were dissolved in 100 mL methanol, and then the Zn(NO3)2·6H2O methanol solution was quickly poured into the 2-methylimidazole methanol solution and stirred for 1 h. The resulting suspension was milky white and then centrifuged at 25 °C (10000 rpm, 10 min), washed with methanol and centrifuged 3 times, and dried at 80 °C in vacuum for 24 h before collecting ZIF-8 nanoparticles. 0.12 g cyanuric acid was dissolved in 100 mL ethanol with stirring at 60 °C for 30 min to form a colorless, transparent, and uniform solution. 0.12 g ZIF-8 powder (average diameter ~100 nm) was added to 20 mL ethanol and the ZIF-8 was dispersed by ultrasonic oscillation to obtain a uniform suspension. The cyanuric acid solution was mixed with the ZIF-8 suspension, and after ultrasonic dispersion, the resulting suspension was stirred at 60°C for 12 or 24 hours to prepare defective ZIF-8 (DZIF-8) with different etching degrees. After the reaction was completed, the etched DZIF-8 was collected by centrifugation, washed several times with anhydrous ethanol, and finally collected after vacuum drying at 80°C for 24 hours.

[0054] (3) Preparation of 5 wt% defective ZIF-8-based mixed matrix membrane: DZIF-8 etched with cyanuric acid was activated in a vacuum oven at 150°C for 3 h. Subsequently, 0.01 g of DZIF-8 was dispersed in 4.8 g of N,N-dimethylformamide using ultrasound. The impurities were filtered out by passing the AO-PIM-1 (0.19 g) solution in which N,N-dimethylformamide (5.0 g) was dissolved through a 10 μm filter membrane. During the blending process, 50% of the AO-PIM-1 solution was added to the DZIF-8 dispersion for primer coating and ultrasonic treatment for 30 min; the remaining 50% of the AO-PIM-1 solution was then added to the mixed solution, stirred for 12 h, ultrasonically degassed for 30 min and allowed to stand for 2 h. Finally, the mixed solution was placed in a glass culture dish and allowed to stand in a 50°C oven for 24 h to evaporate the solvent and form a film.

[0055] Example 2

[0056] (1) Synthesis of AO-PIM-1 polymer: The method is consistent with step (1) in Example 1.

[0057] (2) Synthesis of defective ZIF-8 etched by cyanuric acid: The method is consistent with step (2) in Example 1.

[0058] (3) Preparation of 10 wt % defective ZIF-8-based mixed matrix membrane: the amount of DZIF-8 used was 0.02 g, the amount of AO-PIM-1 used was 0.18 g, and the other methods were the same as step (3) in Example 1.

[0059] Example 3

[0060] (1) Synthesis of AO-PIM-1 polymer: The method is consistent with step (1) in Example 1.

[0061] (2) Synthesis of defective ZIF-8 etched by cyanuric acid: The method is consistent with step (2) in Example 1.

[0062] (3) Preparation of 15 wt % defective ZIF-8-based mixed matrix membrane: the amount of DZIF-8 used was 0.03 g, the amount of AO-PIM-1 used was 0.17 g, and the other methods were the same as step (3) in Example 1.

[0063] Example 4

[0064] (1) Synthesis of AO-PIM-1 polymer: The method is consistent with step (1) in Example 1.

[0065] (2) Synthesis of defective ZIF-8 etched by citric acid: ZIF-8 was synthesized according to step (2) in Example 1. 0.12 g of ZIF-8 powder (average diameter ~100 nm) was added to 20 mL of methanol, and the ZIF-8 was dispersed by ultrasonic oscillation to obtain a uniform suspension. 0.14 g of citric acid was dissolved in 100 mL of ethanol by stirring at room temperature for 30 min to form a colorless, transparent, uniform solution. The citric acid solution was blended with the ZIF-8 suspension, and after ultrasonic dispersion, the resulting suspension was stirred at room temperature for 12 or 24 h to prepare defective ZIF-8 (DZIF-8) with different etching degrees. After the reaction was completed, the etched DZIF-8 was collected by centrifugation, washed several times with anhydrous methanol, and finally collected after vacuum drying at 80°C for 24 hours.

[0066] (3) Preparation of 5, 10, and 15 wt% defective ZIF-8-based mixed matrix membranes: The filler used in the preparation of 5, 10, and 15 wt% DMMM is DZIF-8 etched with citric acid. The amounts of polymer and filler required for the preparation of 5, 10, and 15 wt% DMMM are respectively referred to Examples 1, 2, and 3, and the other preparation methods are the same.

[0067] Example 5

[0068] (1) Synthesis of AO-PIM-1 polymer: The method is consistent with step (1) in Example 1.

[0069] (2) Synthesis of glycine-etched defective ZIF-8: The amount of glycine used was 0.36 g, and the other synthesis steps were consistent with step (2) in Example 4.

[0070] (3) Preparation of 5, 10, and 15 wt% defective ZIF-8-based mixed matrix membranes: The filler used in the preparation of 5, 10, and 15 wt% DMMM is glycine-etched DZIF-8. The amounts of polymer and filler required for the preparation of 5, 10, and 15 wt% DMMM are respectively referred to Examples 1, 2, and 3. The other preparation methods are the same.

[0071] Example 6

[0072] (1) Synthesis of AO-PIM-1 polymer: The method is consistent with step (1) in Example 1.

[0073] (2) Synthesis of defective ZIF-8 etched by gallic acid: The amount of gallic acid used was 0.16 g, and the other synthesis steps were consistent with step (2) in Example 4.

[0074] (3) Preparation of 5, 10, and 15 wt% defective ZIF-8-based mixed matrix membranes: The filler used in the preparation of 5, 10, and 15 wt% DMMM is DZIF-8 etched with gallic acid. The amounts of polymer and filler required for the preparation of 5, 10, and 15 wt% DMMM are respectively referred to Examples 1, 2, and 3, and the other preparation methods are the same.

[0075] Example 7

[0076] (1) Synthesis of AO-PIM-1 polymer: The method is consistent with step (1) in Example 1.

[0077] (2) Synthesis of defective ZIF-8 etched by methyl gallate: The amount of methyl gallate used was 0.15 g, and the other synthesis steps were consistent with step (2) in Example 4.

[0078] (3) Preparation of 5, 10, and 15 wt% defective ZIF-8-based mixed matrix membranes: The filler used in the preparation of 5, 10, and 15 wt% DMMM is DZIF-8 etched with methyl gallate. The amounts of polymer and filler required for the preparation of 5, 10, and 15 wt% DMMM are respectively referred to Examples 1, 2, and 3, and the other preparation methods are the same.

[0079] Comparative Example 1

[0080] (1) Synthesis of PIM-1: The method is consistent with the synthesis of PIM-1 in step (1) of Example 1.

[0081] (2) Preparation of PIM-1 membrane: 0.2 g of PIM-1 was dissolved in 9.8 g of chloroform to prepare a 2 wt% casting solution, which was stirred for 24 h and filtered through a 10 μm filter membrane. The solution was then ultrasonically degassed for 20 min and allowed to stand for 2 h. The solution was finally poured into a glass culture dish and allowed to stand at room temperature for 24 h to evaporate the solvent and form a membrane.

[0082] Comparative Example 2

[0083] (1) Synthesis of AO-PIM-1: The method is consistent with the synthesis of AO-PIM-1 in step (1) of Example 1.

[0084] (2) Preparation of AO-PIM-1 membrane: 0.2 g AO-PIM-1 was dissolved in 9.8 g N,N-dimethylformamide to prepare a 2 wt% casting solution. The solution was stirred for 24 h and filtered with a 10 μm filter membrane. The solution was then ultrasonically degassed for 20 min and allowed to stand for 2 h. The solution was then poured into a glass culture dish and allowed to stand in an oven at 50 °C for 24 h to evaporate the solvent and form a membrane.

[0085] Comparative Example 3

[0086] (1) Synthesis of AO-PIM-1 polymer: The method is consistent with step (1) in Example 1.

[0087] (2) Synthesis of ZIF-8: ZIF-8 was synthesized according to step (2) in Example 1.

[0088] (3) Preparation of 10 wt% ZIF-8-based mixed matrix membrane: ZIF-8 was activated in a vacuum oven at 150°C for 3 h. Subsequently, 0.02 g ZIF-8 was dispersed in 4.8 g N,N-dimethylformamide using ultrasound. The AO-PIM-1 (0.18 g) solution in which N,N-dimethylformamide (5.0 g) was dissolved was filtered through a 10 μm filter membrane to remove impurities. During the blending process, 50% AO-PIM-1 solution was added to the ZIF-8 dispersion for primer coating and ultrasonic treatment for 30 min; the remaining 50% AO-PIM-1 solution was then added to the mixed solution, stirred for 12 h, ultrasonically degassed for 30 min and allowed to stand for 2 h. Finally, the mixed solution was placed in a glass culture dish and allowed to stand in a 50°C oven for 24 h to evaporate the solvent and form a membrane.

[0089] The propylene propane permeability and selectivity of the gas separation membrane prepared by the control examples 1-3 and the examples 1-3 are shown in Table 1. By comparing the control examples with the examples, it can be found that the DMMMs (5%, 10%, 15%) prepared by the examples 1-3 exhibited more excellent separation performance. Specifically, compared with the AO-PIM-1 base membrane, DZIF-8 performed more significantly than ZIF-8 in improving membrane selectivity, but the permeability decreased. This may be because the amidoxime groups in AO-PIM-1 coordinated with the exposed metal sites of DZIF-8, greatly enhancing the interfacial interaction between the two phases, thereby improving the gas screening performance, but also increasing the resistance of the gas channel, resulting in a decrease in permeability. In addition, the exposed metal sites of DZIF-8 provide additional propylene adsorption sites, further enhancing the selectivity of DMMMs. Specifically, the permeability of 10% DMMMs decreased by 55% and the selectivity increased by 200% compared with AO-PIM-1; compared with 10% MMMs, the permeability decreased by 64% and the selectivity increased by 114%.

[0090] Table 1 shows the propylene propane permeability and selectivity of the gas separation membranes prepared in the control example and the example.

[0091]

Claims

1. A method for preparing a defective MOF-based self-microporous polymer mixed matrix membrane for efficient separation of propylene and propane, characterized in that: Here are the steps: (1) Synthesis of MOFs; (2) Acid etching of MOF: dissolving acid A in solvent A to obtain a colorless transparent solution; dispersing the MOF nanoparticles synthesized in step (1) in solvent A, and obtaining a uniform MOF suspension after ultrasonication; blending the colorless transparent solution with the MOF suspension, stirring the mixture at a certain temperature, collecting the mixture by centrifugation, washing the mixture with solvent A, centrifuging the mixture several times, and drying the mixture in a vacuum oven to obtain defective MOF particles after etching; (3) Synthesis of amidoxime PIM-1: 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, tetrafluoroterephthalonitrile and anhydrous potassium carbonate are added to a mixed solution of solvent B and solvent C, stirred at room temperature to fully disperse, and then reacted at a certain temperature under the atmosphere of protective gas A; after the reaction, the product is washed with solvent A, dissolved in solvent D and allowed to stand, and then solvent A is added to precipitate, then washed with deionized water, and finally vacuum dried in a vacuum oven to obtain a purified PIM-1 polymer; the synthesized PIM-1 polymer is dissolved in solvent E, heated and dissolved in the atmosphere of protective gas A, and after the temperature gradually rises to the reaction temperature, a 50wt% hydroxylamine aqueous solution is added dropwise to perform a reflux reaction; after the reaction is completed, it is cooled to room temperature, the reactant is poured into solvent A for precipitation, vacuum filtered and washed with solvent A, and finally vacuum dried in a vacuum oven to obtain a flocculent or powdery AO-PIM-1 polymer; (4) Preparation of AO-PIM-1 membrane: AO-PIM-1 polymer was dissolved in solvent F to prepare a membrane casting solution, stirred to fully dissolve, filtered through a microporous membrane filter, and then ultrasonically defoamed. The solution was placed in an oven at a certain temperature to volatilize the solvent and form a membrane; (5) Preparation of DMMM: The defective MOF synthesized in step (2) is activated in a vacuum drying oven and ultrasonically dispersed in solvent H to obtain a defective MOF dispersion; AO-PIM-1 is dissolved in solvent F; the AO-PIM-1 solution filtered through a microporous membrane filter is mixed with the defective MOF dispersion, and the AO-PIM-1 solution is added to the defective MOF dispersion twice to prepare a casting solution, which is initially dispersed by ultrasound, stirred to be fully dispersed, and then ultrasonically degassed. After standing, the solution is poured into a culture dish and allowed to stand at a certain temperature in an oven to volatilize the solvent to form a film.

2. The preparation method according to claim 1, characterized in that: The specific process of synthesizing MOF in step (1) is as follows: Disperse metal salt A and 2-methylimidazole in the reaction medium respectively, and quickly pour the metal salt A solution into the 2-methylimidazole solution for stirring reaction to obtain a milky white suspension; Centrifuge the mixture, wash and centrifuge it several times for purification, and dry it in a vacuum oven to obtain MOF nanoparticles. Wherein, the metal salt A is zinc nitrate hexahydrate and / or cobalt nitrate hexahydrate; The reaction medium is methanol and / or ethanol; The molar ratio of metal salt A to 2-methylimidazole is 1:2-16; The reaction temperature is 25°C; The speed of the centrifuge was 10000 rpm, and the centrifugation time was 10 min; The solvent used for washing was methanol; The drying temperature is 80°C and the drying time is 24 hours.

3. The preparation method according to claim 1, characterized in that: In step (2), Wherein, acid A is one or a mixture of two or more of cyanuric acid, citric acid, glycine, gallic acid, and methyl gallate; Solvent A is methanol and / or ethanol; The molar ratio of acid A to MOF nanoparticles is 1:1-8; The reaction time is 12-36h, and the reaction temperature is 25-80°C; The speed of the centrifuge was 10000 rpm, and the centrifugation time was 10 min; The drying temperature is 80°C and the drying time is 24h.

4. The preparation method according to claim 1, characterized in that: In step (3), The molar ratio of 5,5',6,6'-tetrahydroxy-3,3,3',3'-tetramethyl-1,1'-spirobiindane, tetrafluoroterephthalonitrile and anhydrous potassium carbonate is 1:1:3; solvent B and solvent C are N,N-dimethylacetamide and toluene, respectively, with a mass ratio of 2:1; Solvent D is chloroform; Solvent E is tetrahydrofuran; Protective gas A is nitrogen; The reaction temperature for synthesizing the PIM-1 polymer was 155°C and the reaction time was 60 min; The drying temperature of PIM-1 for synthesizing PIM-1 polymer was 120°C and the drying time was 24 h; The reaction temperature for synthesizing AO-PIM-1 polymer was 69°C and the reaction time was 2 h; The dropping rate of the hydroxylamine aqueous solution was 1 mL / min; The drying temperature of AO-PIM-1 was 120°C and the drying time was 24 h.

5. The preparation method according to claim 1, characterized in that: In step (4), Wherein, solvent F is N,N-dimethylformamide and / or N,N-dimethylacetamide; The mass fraction of AO-PIM-1 polymer in the casting solution is 2-5wt%; The stirring time is 12-24h, and the ultrasonic time is 20min; The evaporation temperature of the solvent is 50°C and the evaporation time is 24h.

6. The preparation method according to claim 1, characterized in that: In step (5), Among them, the ultrasound time was 30min; The stirring time is 12-24h, and the standing time is 2h; The temperature of the oven is 50°C and the volatilization time is 24h.

Citation Information

Patent Citations

  • Preparation method of PIM-1 mixed matrix membrane based on amidoxime group modified UiO-66 material

    CN115228311A

  • Uniformly-distributed defect-free c-PIMs / MOFs composite membrane as well as preparation method and application thereof

    CN119236719A

  • Porous membrane and manufacturing method thereof, and gas separation system

    JP2024135023A

  • Membrane composites, methods and uses thereof

    WO2022173375A1